Patterns and Challenges of Family Life Course Sequences in Lithuania and Europe - Indriliūnaitė, Rasa; Žilys, Apolonijus (Socialinė teorija, empirija, politika ir praktika, 2026)
The goal of this article is aimed at the identification of the behaviour, attitudes and beliefs of the Lithuanian population towards several key events at the start of adult life course, i.e., when it is the most appropriate to initiate the first events of cohabitation with partner, marriage union, and becoming a parent, and when these events have been completed. Conceptually, the article assesses the extent to which these attitudes are influenced by normative cultural attitudes, and how the so-called ‘standard’ sequence of family life events (partnership, marriage, childbearing) is accessible to maintain. Furthermore, it has been examined to what extent the family life scenarios identified in the Lithuanian population are close to the scenarios in other European countries. The empirical part of the paper is based on analysis from the European Social Survey (ESS) Round 9 data. The research was conducted by using various methods – from descriptive sequencing data to regression analysis. The results show that only a minor proportion of the respondents consider that their family life has been started in a timely manner, while the sequence of the life course for most Lithuanians does not coincide with their expectation and perception of the most appropriate time to start those events. These discrepancies provide evidence to the general assumption about the uneven development of modern Lithuanian society and the different experiences of structural changes between generations which have conditioned the different implementation of important demographic events (e.g., delaying marriage) across generations.